2012
DOI: 10.1002/pi.4355
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of microcellular polymer/graphene nanocomposite foams

Abstract: Graphene has recently gained revolutionary aspirations because of its remarkable electronic, thermal and mechanical properties. These unique properties make it promising for preparing multifunctional nanocomposites. In recent years, polymer foams based on graphene have also received increasing attention in both the scientific and industrial communities. This review presents an overview of polymer/graphene nanocomposite foams discussing the production of graphene, the polymer functionalization of graphene and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 67 publications
0
27
0
1
Order By: Relevance
“…Thus, foaming processing conditions play an essential role in the final morphological/microstructural characteristics of the resulting foams. On the other hand, several studies have indicated that a small amount of well-dispersed nanoparticles can act as cell nucleation sites and that nucleation efficiency is dependent on particle size, shape, surface properties and dispersion quality [2,4,9]. In addition, it has been shown that the combination of graphene nanoplatelets and scCO 2 during foaming may have remarkable effects on the microstructure of the developed foams [10].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, foaming processing conditions play an essential role in the final morphological/microstructural characteristics of the resulting foams. On the other hand, several studies have indicated that a small amount of well-dispersed nanoparticles can act as cell nucleation sites and that nucleation efficiency is dependent on particle size, shape, surface properties and dispersion quality [2,4,9]. In addition, it has been shown that the combination of graphene nanoplatelets and scCO 2 during foaming may have remarkable effects on the microstructure of the developed foams [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two scCO 2 dissolution temperatures were considered: 80 and 100 ºC, in both cases applying a dissolution time of 210 min. The scCO 2 was initially introduced in the vessel at 70 bar, reaching a final dissolution pressure of 140 and 180 bar, respectively for 80 and 100 ºC. Once carbon dioxide was dissolved into the foam precursors, these were cooled down to room temperature by re-circulating water through the vessel's cooling jacket while keeping the vessel pressurized at 15 ºC/h in order to avoid undesirable pre-foaming.…”
Section: Foaming Process: Stage I -Supercritical Carbon Dioxide Dissomentioning
confidence: 99%
See 3 more Smart Citations